Evaluation of Factor Xa-Specific Chromogenic Substrate Assays and the Determination of Pharmacokinetics of Fondaparinux. (July 2016) - Yuri, Maiko; Tabe, Yoko; Tsuchiya, Koji; Sadatsuki, Ryo; Aoki, Jun; Horii, Takashi; Iba, Toshiaki; Ohsaka, Akimichi
Fondaparinux (FPX), a synthesized factor Xa inhibitor, is one of the most popular anticoagulants for the prevention of postoperative venous thromboembolism (VTE). Although routine monitoring is not required, the bleeding adverse events cannot be neglected, and the measurement of anti-Xa activity is expected to be monitored. The primary purpose of this study is to evaluate the performances of 2 chromogenic assays for the detection of anti-Xa activity. Furthermore, the pharmacokinetics of FPX was examined using chromogenic assays. Anti-Xa activity was measured using 2 FPX-based chromogenic substrates (S2222 and STA-Liquid Anti-Xa). The reproducibility, detection limits, linearity, and correlations between the substrates were examined using normal plasma doped with low and high concentrations of FPX formulation. In addition, anti-Xa activity in 235 clinical samples from 164 cases treated was measured, and the pharmacokinetics of FPX was evaluated. Both of the tested substrates were capable of accurately measuring the anti-Xa activity of FPX, with a lower limit of 0.05 μg/mL and a coefficient of variation of less than 10%. The repeated administration of FPX induced a gradual but significant increase in the anti-Xa activity, which was negatively correlated with body weight and estimated glomerular filtration rate. No significant correlation between the anti-Xa activity and the occurrence of postoperative VTE or bleeding event was observed. Anti-Xa activity can be successfully determined using 2 chromogenic assays and automated biochemical analyzers. The clinical significance of anti-Xa activity monitoring should be examined in the future study.